بلوچی غزل کا ارتقاء: The evolution of Balochi Ghazal - Bano, Surya (Hanken, 2009)
The history Balochi Poetry is very ancient and deep rooted but the history of lyric is very new and earlier. The lyric is not a native style of the Balochi literature but has come from the neighboring languages like. Persian and Urdu. In the passage of time, the Baloch lyric has developed and introduced itself a different and unique style among the neighboring languages. IN the modern poetry, the Balochi Lyric Has identified itself provided a major portion to the Balochi Literature.